Introduction to the Mechanics of Deformable Solids Bars and Beams - H. Allen, David (Springer New York : Imprint: Springer, 2013)
Introduction to the Mechanics of Deformable Solids: Bars and Beams introduces the theory of beams and bars, including axial, torsion, and bending loading and analysis of bars that are subjected to combined loadings, including resulting complex stress states using Mohr's circle. The book provides failure analysis based on maximum stress criteria and introduces design using models developed in the text. Throughout the book, the author emphasizes fundamentals, including consistent mathematical notation. The author also presents the fundamentals of the mechanics of solids in such a way that the beginning student is able to progress directly to a follow-up course that utilizes two- and three-dimensional finite element codes imbedded within modern software packages for structural design purposes. As such, excessive details included in the previous generation of textbooks on the subject are obviated due to their obsolescence with the availability of today's finite element software packages. This book also: Features a highly visual pedagogy that emphasizes how visual representation of models leads to mathematical models Pays careful attention to the history of mechanics and includes a historical chapter Includes a separate chapter on structural design Maintains congruity of notation and approach to all mechanics models Features 200 illustrations Introduction to the Mechanics of Deformable Solids: Bars and Beams is an ideal book for undergraduate students taking their first course in mechanics of solids.